Scoping review of the literature on outcomes of the conservation reserve program - Mark P. Nessel; Karen Maguire; Rich Iovanna; Courtney J. Duchardt; Scott R. Loss (PLoS ONE, 2025)
The Conservation Reserve Program (CRP), one of the largest private lands conservation programs in the U.S., has played a critical role in soil erosion reduction, water quality improvement, wildlife habitat enhancement, and carbon sequestration since its inception in 1985. This paper contributes to the extensive research illustrating the benefits of the program by providing a scoping review of the peer-reviewed CRP literature. We conduct a broad-scale examination of the literature on CRP, identifying the gaps and trends in this literature to inform future research on this program. Through systematic analysis of 577 studies, we examined spatial and temporal trends in the literature, categorized CRP research into five major categories—including studies of wildlife, vegetation, air/soil/water, productivity, and social aspects—and conducted a detailed evaluation of the CRP outcomes in the wildlife and vegetation categories. For studies of wildlife-related outcomes of CRP we found studies of birds to dominate the literature, while research on other taxa such as fish, reptiles, and amphibians remains sparse. Geographically, most studies are concentrated in the Great Plains, leaving regions such as the Pacific Northwest underrepresented relative to CRP land share. This review highlights the need for long-term studies and additional research, including less-studied taxa and underrepresented regions, to better understand CRP’s potential for enhancing biodiversity and ecosystem services.